Sound, sense, and story : narrativity and poeticity in the contemporary lyric poem - Wee, Samuel Ting Han (2018)
This thesis explores the questions of how narratives are generated uniquely through the mechanisms of poetry and investigates the history of narrative theory and its orientation towards poetry. This thesis makes three main claims: firstly, that poetry is indeed very much capable of generating narrative; secondly, that the existing theoretical toolbox of narrative theory is inadequate to properly articulate the mechanics of narrative generation in poetry; and thirdly, that a synthesis of poetics and narrative theory is necessary for this aspect of literary poesis to be properly understood. Being primarily a theoretical work, it takes for its primary material a series of narrative theory and poetics texts, including the work of Brian McHale, James Phelan, Monika Fludernik, Rachel Blau DuPlessis, Giorgio Agamben, John Shoptaw, Majorie Perloff, and David Herman. These theoretical texts are investigated comparatively from a meta-hermeneutical perspective (in the vein of Rita Felski and Derek Attridge) and surveyed to construct a new theoretical model that fits our reading purposes. Said theoretical model is thus applied to a series of poetic texts of varying lengths and styles to test the robustness of the method: these texts are Arthur Yap’s “sociability”, Derek Mahon’s The Hudson Letter, John Ashbery’s “Self-Portrait in a Convex Mirror”, and Desmond Kon Zhicheng-Mingdé’s The Wrong/Wrung Side of Love. Over the course of reading these texts from the re-designed theoretical model proposed in this dissertation, the argument is made that poetry’s unique quality of being structured around what DuPlessis terms “organised pauses or silences” renders it phenomenologically unique. We conclude on the argument that poetry demands a conscientious receptiveness to alterity and a sensitive attendance to form that require the reader to enter into a creative co-writing of the text with the author.